Mobile learning: using SMS in educational contexts. - Moura, Adelina (2010)
The Short Message Service (SMS) technology is one of the most powerful mobile technologies in current usage. Most students own a mobile phone with free SMS which can be used for learning. In this paper we explain how we used SMS for teaching and learning languages (both native and foreign). The conducted experiment presented a range of opportunities for integrating text into teaching and learning strategies and for demystifying the use of SMS in educational contexts. Via SMS technology we can deliver several learning activities to students easily and immediately. The research findings showed that students had positive perceptions about the experiment and SMS use for learning improvement and the use of their own mobile phone as a learning tool. All groups showed interest in receiving educational content via SMS. Some students greatly improved their language learning performance.